A review of the "browni group" of Penaincisalia with notes on their distribution and variability (Lepidoptera: Lycaenidae: Eumaeini) - Prieto, Carlos; Bálint, Zsolt; Boyer, Pierre; Micó, Estefanía (Zootaxa, 2008)
We provide a taxonomic review of the “browni group”, a cloud forest lineage of the diverse lycaenid butterfly genus Penaincisalia, distributed from Costa Rica to northern Argentina. The group is characterized on the basis of five characters provided by wing shape, forewing androconia and genital structures. We distinguish eight species in the group: P. browni (Johnson, 1992), P. caeruleonota Hall & Willmott, 2005; P. cuiva Prieto & Rodriguez, 2007; P. magnifica (Johnson, 1992), P. purpurea (Johnson, 1992), P. saraha (Johnson, 1992), P. vittata (Johnson, 1992) and P. regala (Le Crom & Johnson, 1997). We confirm their status as presented in the recent Checklist of Neotropical Butterflies (Robbins, 2004), except for P. regala which is reinstated to species status from synonymy. The taxonomic history of each species with references to type material is provided. Every species is diagnosed, male and female phenotypes are associated, described and data on their distribution and biology are given. If relevant the variability of the species is discussed.